Characterization of prepared soft-shelled turtle dishes of different pretreatment combined with irradiation based on flavor profiles usingE-nose, E-tongueand HS-SPME-GC–MS - Yuanfang Xu; Xiaoyu Wang; Qingxiu Mao; Qiling Zhang; Yiji Zhou; Gaoliu Huang; Lu Liu; Qing Yang; Yong Zhang; Feng Guo; Chao Deng; Meijuan Yu; et al. (Food Chemistry: X)
The effects of different pretreatment combined with irradiation on the flavor profiles of prepared soft-shelled turtle dishes were explored by using electronic nose, electronic tongue and headspace solid-phase microextraction gas chromatography–mass spectrometry (HS-SPME-GC–MS). The results showed that electronic nose analysis indicated distinct odor profiles before and after irradiation, with PCA effectively differentiating them. The low-temperature pretreatment group had the smallest difference from the control (CK). After 180 days of storage, odor profiles of all samples converged, with low-temperature, 0.1 % rosemary, and 0.1 % TBHQ groups showing minimal differences from CK. Electronic tongue profiles showed no significant differences among treatments, with PCA unable to effectively distinguish most groups, except for the 0.1 % rosemary and 0.1 % sesamol groups. The results of HS-SPME-GC–MS analysis showed that the volatile compounds of the samples of each treatment were significantly different. The 6 kGy (kilogray) irradiation group, the low temperature pretreatment and the control group (CK) clustered into one category. After 180 d of storage at room temperature, only the low temperature pretreatment group and the control group (CK) were clustered into one category. The results of relative odor activity value (ROAV) showed that the key flavor compounds of prepared soft-shelled turtle dishes were heptanal, octanal, (E)-2-octenal, nonanal, (E,E)-2,4-nonadienal, decanal, (E)-2-decenal, (E,E)-2,4-decadienal, 2-undecanal, 1-octen-3-ol, and 2-pentylfuran. Aldehydes contents in the samples increased after irradiation, which was the main components leading to the off-odor of prepared soft-shelled turtle dishes after irradiation, and the key flavor compounds of the samples decreased after 180 d of storage at room temperature. In conclusion, low temperature or pretreatment of three antioxidants could maintain the flavor of prepared soft-shelled turtle dishes after irradiation, and low temperature had the best effect. This study could provide theoretical reference for the application of irradiation technology in the sterilization and preservation processing of prepared soft-shelled turtle dishes and its flavor control.